La Gestion Colectiva de los Derechos Patrimoniales Derecho de Autor y Derechos Conexos (Revista de Derecho, 2012)
DOI: http://dx.doi.org/10.5377/derecho.v0i3.723 Revista de Derecho No.3 2002 pp.221-240